Compatibility of religion and science - Wakhid Hasyiem Pratama Aji; Sukri, Ridwan Ahmad (Journal of Islam and Science, 2023)
Science and religion are regarded as two conflicting entities within the Western cultural paradigm, particularly among naturalists. The claims made by religion regarding supernatural entities are rejected by naturalist groups, who emphasize their arguments based on science. However, within the perspective of Islamic culture, there exists a close relationship between science and religion. Science and religion are two entities that exist on the same path and cannot be pitted against each other. The author will present Alvin Plantinga's arguments against Richard Dawkins regarding the compatibility of science and religion, as Dawkins, being a naturalist, deems them incompatible. The author will also put forth arguments by Naquib Al-Attas concerning the inseparable relationship between science and religion. In conclusion, the differing understandings of religion and science give rise to conflicts between perspectives. The methodology employed by the author is theoretical and comparative descriptive, involving the explanation of prominent figures' thoughts on a subject and the comparison of these thoughts to identify the fundamental issues stemming from differences in their perspectives.